2005
DOI: 10.1002/asna.200410349
|View full text |Cite
|
Sign up to set email alerts
|

Light‐time effect in the eclipsing binary system AM Leonis

Abstract: Abstract. We report four new times of minimum light and the improved ephemeris for the well known contact binary AM Leo. The O-C diagram, constructed with all reliable timings found in the literature was analyzed and the the light-time effect in the system was confirmed. We found a periodicity of 44.82 years in the O-C residuals with an amplitude of 0.0058 day. The periodic curve representing the O-C values is asymmetric indicating a large eccentricity of 0.73 of the third body orbit. The mass of the third bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The recent period study of AM Leo (Albayrak et al 2005) shows possible cyclic period variations, interpreted by the authors as a result of a LITE caused by an invisible third component with a minimum mass of 0.18 M . The authors estimated that this hypothetical body would be about 7 mag (i.e., more than 600 times) fainter than the contact binary.…”
Section: Am Leomentioning
confidence: 96%
See 1 more Smart Citation
“…The recent period study of AM Leo (Albayrak et al 2005) shows possible cyclic period variations, interpreted by the authors as a result of a LITE caused by an invisible third component with a minimum mass of 0.18 M . The authors estimated that this hypothetical body would be about 7 mag (i.e., more than 600 times) fainter than the contact binary.…”
Section: Am Leomentioning
confidence: 96%
“…The radial velocity of the visual companion, V 3 = −11.08 ± 0.97 km s −1 , was found to be stable and close to the systemic velocity of the eclipsing binary. Due to the relatively high brightness of the eclipsing pair, it was a subject of numerous photometric investigations (for references see Hiller et al (2004); Albayrak et al (2005)). Hiller et al (2004) analyzed the light curves of the system and found q = 0.398 and the inclination angle i = 86 • .…”
Section: Am Leomentioning
confidence: 99%
“…They also suggested that the mass ratio is q ph = 2.51 = 1/0.398 (inverted for a W‐subtype contact binary). Albayrak et al (2005a) showed possible cyclic‐period variations, due to the existence of a third body, orbiting the contact binary in 44.82 yr and having a mass of M 3 = 0.175 M ⊙ . Qian & Yang (2005) studied the orbital variation of the system through the (O–C) diagrams.…”
Section: Introductionmentioning
confidence: 99%